Basal area growth models for Eucalyptus tereticornis Smith stands on the Colombian Atlantic coast - Barrios-Trilleras, Alonso; López-Aguirre, Ana Milena (Instituto de Ecología, A.C., 2020)
Eucalyptus tereticornis is an important species used in reforestation programs in Colombia. Information on the dynamics and development of the E. tereticornis stands is required to improve management planning. This study compares nine basal area growth models, evaluating their goodness of fit and prediction, and describes their linkage to a thinning response model for E. tereticornis plantations. The evaluated models showed a good fit to the data, the R2adj ranged between 0.90 - 0.92 and 0.69 - 0.86 for the basal area projection and prediction models, respectively. The root of the mean square error (RMSE) ranged between 1.080 m2 ha-1 - 1.343 m2 ha-1 for basal area projection models and 1.671 m2 ha-1 - 2.206 m2 ha-1 for basal area prediction models. The selected basal area model for unthinned stands depends on the age, stand density, and dominant height. For the thinned stands, the basal area was predicted using a competition index that depends on the age and the dominant height of the stand. The competition index had an R2adj = 0.87, and a standard error of estimate of 0.031%. The system of equations presented a slight tendency to overestimate with a mean error of -0.14 m2 ha-1 and a RMSE of 0.696 m2 ha-1. This way, the developed models have the potential to be applied to unthinned and thinned stands with different ages, productivity, and planting densities. The developed models provide new tools to support forest management and research of the species growing in plantations.